The solution of the inverse Laplace transforms is mathematically given as
<h3>What is the inverse Laplace transform?</h3>
1)
Generally, the equation for the function is mathematically given as
![$F_{1}(s)=\frac{6 s^{2}+8 s+3}{s\left(s^{2}+2 s+5\right)}$](https://tex.z-dn.net/?f=%24F_%7B1%7D%28s%29%3D%5Cfrac%7B6%20s%5E%7B2%7D%2B8%20s%2B3%7D%7Bs%5Cleft%28s%5E%7B2%7D%2B2%20s%2B5%5Cright%29%7D%24)
By Applying the Partial fractions method
![\frac{6 s^{2}+8 s+3}{s\left(s^{2}+2 s+5\right)}=\frac{A}{s}+\frac{B s+C}{s^{2}+2 s+5}](https://tex.z-dn.net/?f=%5Cfrac%7B6%20s%5E%7B2%7D%2B8%20s%2B3%7D%7Bs%5Cleft%28s%5E%7B2%7D%2B2%20s%2B5%5Cright%29%7D%3D%5Cfrac%7BA%7D%7Bs%7D%2B%5Cfrac%7BB%20s%2BC%7D%7Bs%5E%7B2%7D%2B2%20s%2B5%7D)
![$6 s^{2}+8 s+3=A\left(s^{2}+2 s+5\right)+(B s+C) s$](https://tex.z-dn.net/?f=%246%20s%5E%7B2%7D%2B8%20s%2B3%3DA%5Cleft%28s%5E%7B2%7D%2B2%20s%2B5%5Cright%29%2B%28B%20s%2BC%29%20s%24)
![\begin{aligned}&3=5 A \\&A=\frac{3}{5}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%263%3D5%20A%20%5C%5C%26A%3D%5Cfrac%7B3%7D%7B5%7D%5Cend%7Baligned%7D)
Considers s^2 coefficient
![\begin{aligned}&6=A+B \\&B=6 \cdot A \\&B=\frac{27}{5}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%266%3DA%2BB%20%5C%5C%26B%3D6%20%5Ccdot%20A%20%5C%5C%26B%3D%5Cfrac%7B27%7D%7B5%7D%5Cend%7Baligned%7D)
Consider s coeffici ent
![\begin{aligned}&8=2 A+C \\&C=8-2 A \\&C=\frac{34}{5}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%268%3D2%20A%2BC%20%5C%5C%26C%3D8-2%20A%20%5C%5C%26C%3D%5Cfrac%7B34%7D%7B5%7D%5Cend%7Baligned%7D)
Putting these values into the previous equation
![&F_{1}(s)=\frac{3}{5 s}+\frac{27 s+34}{5\left(s^{2}+2 s+5\right)} \\\\&F_{1}(s)=\frac{3}{5 s}+\frac{27(s+1)}{5\left((s+1)^{2}+4\right)}+\frac{7 \times 2}{10\left((s+1)^{2}+4\right)}](https://tex.z-dn.net/?f=%26F_%7B1%7D%28s%29%3D%5Cfrac%7B3%7D%7B5%20s%7D%2B%5Cfrac%7B27%20s%2B34%7D%7B5%5Cleft%28s%5E%7B2%7D%2B2%20s%2B5%5Cright%29%7D%20%5C%5C%5C%5C%26F_%7B1%7D%28s%29%3D%5Cfrac%7B3%7D%7B5%20s%7D%2B%5Cfrac%7B27%28s%2B1%29%7D%7B5%5Cleft%28%28s%2B1%29%5E%7B2%7D%2B4%5Cright%29%7D%2B%5Cfrac%7B7%20%5Ctimes%202%7D%7B10%5Cleft%28%28s%2B1%29%5E%7B2%7D%2B4%5Cright%29%7D)
By taking Inverse Laplace Transforms
![f_{1}(t)=\frac{3}{5}+\frac{27}{5} e^{-t} \cos (2t) + \frac{7}{10}\\\\](https://tex.z-dn.net/?f=f_%7B1%7D%28t%29%3D%5Cfrac%7B3%7D%7B5%7D%2B%5Cfrac%7B27%7D%7B5%7D%20e%5E%7B-t%7D%20%5Ccos%20%282t%29%20%2B%20%5Cfrac%7B7%7D%7B10%7D%5C%5C%5C%5C)
![f_{1}(t)=e^{-t}\sin (2 t)](https://tex.z-dn.net/?f=f_%7B1%7D%28t%29%3De%5E%7B-t%7D%5Csin%20%282%20t%29)
For B
![$F_{2}(s)=\frac{s^{2}+5 s+6}{(s+4)(s+1)^{2}}$](https://tex.z-dn.net/?f=%24F_%7B2%7D%28s%29%3D%5Cfrac%7Bs%5E%7B2%7D%2B5%20s%2B6%7D%7B%28s%2B4%29%28s%2B1%29%5E%7B2%7D%7D%24)
By Applying Partial fractions method
![\begin{aligned}&\frac{s^{2}+5 s+6}{(s+4)(s+1)^{2}}=\frac{A}{s+1}+\frac{B}{(s+1)^{2}}+\frac{C}{s+4} \\\\&s^{2}+5 s+6=A(s+1)(s+4)+B(s+4)+C(s+1)^{2}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%26%5Cfrac%7Bs%5E%7B2%7D%2B5%20s%2B6%7D%7B%28s%2B4%29%28s%2B1%29%5E%7B2%7D%7D%3D%5Cfrac%7BA%7D%7Bs%2B1%7D%2B%5Cfrac%7BB%7D%7B%28s%2B1%29%5E%7B2%7D%7D%2B%5Cfrac%7BC%7D%7Bs%2B4%7D%20%5C%5C%5C%5C%26s%5E%7B2%7D%2B5%20s%2B6%3DA%28s%2B1%29%28s%2B4%29%2BB%28s%2B4%29%2BC%28s%2B1%29%5E%7B2%7D%5Cend%7Baligned%7D)
at s=-1
![1-5+6=3 B \\\\B=\frac{2}{3}](https://tex.z-dn.net/?f=1-5%2B6%3D3%20B%20%5C%5C%5C%5CB%3D%5Cfrac%7B2%7D%7B3%7D)
at s=-4
![&16-20+6=9 C \\\\&9 C=2 \\\\&C=\frac{2}{9}](https://tex.z-dn.net/?f=%2616-20%2B6%3D9%20C%20%5C%5C%5C%5C%269%20C%3D2%20%5C%5C%5C%5C%26C%3D%5Cfrac%7B2%7D%7B9%7D)
at s^2 coefficient
1=A+C
A=1-C
A=7/9
inputting Variables into the Previous Equation
![\begin{aligned}&F_{2}(s)=\frac{A}{s+1}+\frac{B}{(s+1)^{2}}+\frac{C}{s+4} \\&F_{2}(s)=\frac{7}{9(s+1)}+\frac{2}{3(s+1)^{2}}+\frac{2}{9(s+4)}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%26F_%7B2%7D%28s%29%3D%5Cfrac%7BA%7D%7Bs%2B1%7D%2B%5Cfrac%7BB%7D%7B%28s%2B1%29%5E%7B2%7D%7D%2B%5Cfrac%7BC%7D%7Bs%2B4%7D%20%5C%5C%26F_%7B2%7D%28s%29%3D%5Cfrac%7B7%7D%7B9%28s%2B1%29%7D%2B%5Cfrac%7B2%7D%7B3%28s%2B1%29%5E%7B2%7D%7D%2B%5Cfrac%7B2%7D%7B9%28s%2B4%29%7D%5Cend%7Baligned%7D)
By taking Inverse Laplace Transforms
![f_{2}(t)=\frac{7}{9} e^{-t}+\frac{2}{3} e^{-t}+\frac{2}{9} e^{-4 t}](https://tex.z-dn.net/?f=f_%7B2%7D%28t%29%3D%5Cfrac%7B7%7D%7B9%7D%20e%5E%7B-t%7D%2B%5Cfrac%7B2%7D%7B3%7D%20e%5E%7B-t%7D%2B%5Cfrac%7B2%7D%7B9%7D%20e%5E%7B-4%20t%7D)
For C
![$F_{3}(s)=\frac{10}{(s+1)\left(s^{2}+4 s+8\right)}$](https://tex.z-dn.net/?f=%24F_%7B3%7D%28s%29%3D%5Cfrac%7B10%7D%7B%28s%2B1%29%5Cleft%28s%5E%7B2%7D%2B4%20s%2B8%5Cright%29%7D%24)
Using the strategy of Partial Fractions
![\frac{10}{(s+1)\left(s^{2}+4 s+8\right)}=\frac{A}{s+1}+\frac{B s+C}{s^{2}+4 s+8}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B%28s%2B1%29%5Cleft%28s%5E%7B2%7D%2B4%20s%2B8%5Cright%29%7D%3D%5Cfrac%7BA%7D%7Bs%2B1%7D%2B%5Cfrac%7BB%20s%2BC%7D%7Bs%5E%7B2%7D%2B4%20s%2B8%7D)
![10=A\left(s^{2}+4 s+8\right)+(B s+C)(s+1)](https://tex.z-dn.net/?f=10%3DA%5Cleft%28s%5E%7B2%7D%2B4%20s%2B8%5Cright%29%2B%28B%20s%2BC%29%28s%2B1%29)
S=-1
10=(1-4+8) A
A=10/5
A=2
Consider constants
10=8 A+C
C=10-8 A
C=10-16
C=-6
Considers s^2 coefficient
0=A+B
B=-A
B=-2
inputting Variables into the Previous Equation
![&F_{3}(s)=\frac{2}{s+1}+\frac{-2 s-6}{\left((s+2)^{2}+4\right)} \\\\&F_{3}(s)=\frac{2}{s+1}-\frac{2(s+2)}{\left((s+2)^{2}+4\right)}-\frac{2}{\left((s+2)^{2}+4\right)}](https://tex.z-dn.net/?f=%26F_%7B3%7D%28s%29%3D%5Cfrac%7B2%7D%7Bs%2B1%7D%2B%5Cfrac%7B-2%20s-6%7D%7B%5Cleft%28%28s%2B2%29%5E%7B2%7D%2B4%5Cright%29%7D%20%5C%5C%5C%5C%26F_%7B3%7D%28s%29%3D%5Cfrac%7B2%7D%7Bs%2B1%7D-%5Cfrac%7B2%28s%2B2%29%7D%7B%5Cleft%28%28s%2B2%29%5E%7B2%7D%2B4%5Cright%29%7D-%5Cfrac%7B2%7D%7B%5Cleft%28%28s%2B2%29%5E%7B2%7D%2B4%5Cright%29%7D)
Inverse Laplace Transforms
![f_{3}(t)=2 e^{-t}-2 e^{-2 t} \cos (2 t)-e^{-2 t} \sin (2 t)](https://tex.z-dn.net/?f=f_%7B3%7D%28t%29%3D2%20e%5E%7B-t%7D-2%20e%5E%7B-2%20t%7D%20%5Ccos%20%282%20t%29-e%5E%7B-2%20t%7D%20%5Csin%20%282%20t%29)
Read more about Laplace Transforms
brainly.com/question/14487937
#SPJ4